An experimental study on the behavior of fiber-reinforced concrete flexural members under cyclic loading - Gatabi, Hamed Rajabzadeh; Celikag, M.; Akbarzadeh Bengar, Habib (Institute of Physics Publishing helen.craven@iop.org, 2020)
An experimental work was performed to address the cyclic performance of reinforced concrete flexural members containing steel, PVA, and Forta-Ferro fibers. Four full-scale reinforced concrete flexural members having the same geometry were subjected to a one-point bending test with slow cyclic loading. One of the four specimens was a control specimen with 0% fiber volume fraction (Vf), and the other three contained 1.5, 0.6, and 1.5% Vf of steel, Forta-Ferro, and PVA fibers, respectively. The ultimate resistance, ductility, stiffness, dissipation of energy was studied, and the influence that different fibers had on the cyclic performance was evaluated. In general, the cyclic performance of the reinforced concrete flexural members improved by adding fibers, leading to higher ultimate displacement and maximum strength value. © Published under licence by IOP Publishing Ltd.
5th International Conference on New Advances in Civil Engineering, ICNACE 2019 -- 2019-11-08 through 2019-11-10 -- Kyrenia -- 160101